Sirenomelia: A new type, Showing VACTERL Association with thomas syndrome and a review of literature. Issue 3 (23rd March 2013) - Lhuaire, Martin; Jestin, Agnès; Boulagnon, Camille; Loock, Mélanie; Doco‐Fenzy, Martine; Gaillard, Dominique; Diebold, Marie‐Danièle; Avisse, Claude; Labrousse, Marc
Abstract Sirenomelia or "mermaid syndrome" is a rare congenital anomaly known since antiquity. This congenital anomaly is defined as a polymalformative syndrome that associates major muscle and skeleton abnormalities (unique lower limbs) with visceral abnormalities (unilateral or bilateral renal agenesis, anomalies of the abdominal vascularisation). This phenotype, typical of sirenomelia syndrome, may be more or less severe. The pathogenic mechanisms of this syndrome are still debated and its etiology remains unknown. We report here a new type of sirenomelia that we observed in a fetus belonging to the collection of the Department of Anatomy of Reims, which led us to perform a comprehensive review of the literature on the subject: this type has never been reported and cannot be classified according to the Stocker and Heifetz classification. Moreover, this case also presents a VACTERL association with Thomas syndrome. Birth Defects Research (Part A) 97:123–132, 2013. © 2013 Wiley Periodicals, Inc.